Restorative Justice in Criminal Law: Global Perspectives and Local Practices - Dr. Prabhat Kumar, Urmi Choudhury, Dr. Umesh Kumar, Nidhi Sharma (Journal of Daoist Studies, 2026)
Restorative justice (RJ) has become an interesting paradigm shift in the criminal law sphere, as it shifts the emphasis on punitive sanctions towards healing-oriented communications between the offender, victims, and communities. The paper offers an extensive study at multiple jurisdictions which examines how restorative justice functions across six continents through its legislative and research and socio-cultural aspects. The paper demonstrates that RJ interventions decrease recidivism rates by 25-30% in all studied contexts after reviewing more than 60 national programs and conducting a systematic analysis of 142 peer-reviewed studies which were published between 2010 and 2023. The intervention results in statistically significant positive outcomes for victim satisfaction which ranges from 68 to 80 percent; it leads to better offender accountability and provides cost-efficient solutions which exceed the financial benefits of custodial sentencing. The paper charts the range of RJ modalities victim-offender mediation (VOM), community conferencing, sentencing circles, and hybrid court-annexed schemes and assesses how they are incorporated into legal systems. The paper evaluates in a critical manner the implementation barriers such as under-resourcing, lack of cultural fit, and net-widening worries. The transformational possibilities and structural constraints of localised RJ practice are clarified by comparative case study in New Zealand, South Africa, Canada, Rwanda, India and Germany. The findings promote an evidence-based extension of the restorative mechanisms in criminal justice reform agendas supported with the help of strong legislative requirements, professional training, and continuous longitudinal assessment.